Ekstrak Bunga Telang (Clitoria ternatea L.) Menghambat Peningkatan Ekspresi Gen MMP-1 pada Kulit Tikus Wistar yang Terpapar Sinar Ultraviolet B - Prasetyowati Subchan; Rizka Sofyanti Putri; Christine Magdalena; Nurul Hidayah (Journal of Midwifery and Health Science of Sultan Agung, 2022)
Background: Photoaging increases MMP-1 and damages collagen by forming ROS. Antioxidant compounds in Clitoria ternatea L. have been studied to reduce ROS, thereby inhibiting the emergence of MMP-1 and regulating collagen deposition. This study aimed to analyze the effect of Clitoria ternatea L. extract gel on the inhibition of MMP-1 increase and collagen decrease in male Wistar rat skin exposed to UV-B light. Methods: A randomized control group post-test-only design was conducted on 30 male Wistar rats aged 8-10 weeks with a body weight of 150-250 grams. Rats were divided into four groups: untreated group, placebo group, Clitoria ternatea L. extract gel group 5% and Clitoria ternatea L. 10% extract gel group. Rats were exposed to UVB for 5 consecutive days and administrated with gel every day for two weeks. At week 3, their skin was checked for MMP-1 levels using q-RTPCR. Results: Comparative analysis showed that the lowest mean MMP-1 levels were seen in the untreated grou, followed by the Clitoria ternatea L. 10% gel extract group, 5% Clitoria ternatea L. extract gel group and placebo group. Comparative analysis showed significant differences between groups (p < 0.05). Conclusion: Clitoria ternatea L. 10% extract gel was proven to inhibit the increase in MMP-1 levels in the skin of Wistar rats exposed to UV-B rays.